Association between HBs Ag quantification and the risk of hepatocellular carcinoma in patients treated with tenofovir disoproxil fumarate or entecavir. Issue 39 (1st October 2021) - Lim, Jung Hyun; Yu, Jung Hwan; Suh, Young Ju; Lee, Jin-Woo; Jin, Young-Joo
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: This study evaluated the clinical implications of hepatitis B surface antigen quantification (qHBs Ag) in chronic hepatitis B (CHB) patients treated with entecavir (ETV) or tenofovir disoproxil fumarate (TDF) and identified the association between qHBs Ag and the risk of hepatocellular carcinoma (HCC) in these patients. Between January 2007 and December 2018, the qHBs Ag and clinical data of 183 CHB patients who initially received ETV (n = 45, 24.6%) or TDF (n = 138, 75.4%) were analyzed. The mean follow-up period of the 183 CHB patients was 45.3 months, of which 59 (32.2%) patients showed a reduction in qHBs Ag by >50% after 1 year of antiviral treatment (ETV or TDF). The HCC development ( P  = .179) or qHBs Ag reduction ( P  = .524) were similar in the ETV and TDF groups. Patients with a ≥50% decrease in qHBs Ag had a significantly lower incidence of HCC or decompensated cirrhosis complications ( P  = .005). Multivariate analysis showed that a >50% reduction of qHBs Ag (hazard ratio 0.085, P  = .018) and the presence of cirrhosis (hazard ratio 3.32, P  = .016) were independent factors predicting the development of HCC. Patients whose qHBs Ag value decreased >50% at 1 year after antiviral treatment for CHB showed a significant decrease in HCC or decompensated cirrhosis events. A reduction in qHBs Ag could be used as a predictive factor of HCC development or critical complications in CHB patients treated with TDF or ETV.